The limbus in developmental dysplasia of the hip: An obstacle to reduction and its images changed by the femoral head position. Issue 51 (23rd December 2021) - Lee, Soon Hyuck; Ahn, Kyung-Sik; Jung, Hae Woon; Jang, Woo Young
Abstract : Abstract: This study aimed to describe the shape of the limbus arthroscopically and via arthrogram and magnetic resonance imaging (MRI), and to determine whether it prevents concentric reduction of the femoral head in developmental dysplasia of the hip (DDH). Twelve patients (mean age, 10.2 months; range, 3–31 months) who underwent arthroscopic-assisted reduction for DDH were retrospectively reviewed. Limbus shapes were captured on arthrogram before reduction, after closed reduction, and after arthroscopic-assisted reduction and categorized according to the Miyake classification. On arthrogram, the superior limbus was blocked in 2 hips, inverted in 2, intermediate in 5, and everted in 3 after attempted closed reduction. After arthroscopic-assisted reduction, the limbus was everted in 7 hips and normal in 5. On arthroscopy, in all cases, the limbus appeared as a whitish, cartilage-like ring with a variably blunted edge before reduction, without inversion or eversion. On postoperative MRI, 10 of 12 superior limbi showed hypertrophy or globular compression by the femoral head with intermediate or mixed MRI signal intensities and blunted edges. The remaining 2 hips had hypertrophied superior limbi with sharp edges. On transverse plane MRI, the posterior limbus of all hips showed sharp margins with low MRI signal intensity. Residual subluxation was observed in 7 of the 12 hips with interposition of the anteroinferior limbus. The appearance of the limbus varied according to the femoral head position, and it was neither inverted nor everted. Interposed anteroinferior limbi with residual subluxation suggest impeded concentric reduction in DDH.